Enhancing Sharaf Mastery Through Ristek Muslim Digital Dictionary and Google Classroom Among Arabic Language Students - Rahman, Aulia; Ainin, Moh; Rosyidi, Abdul Wahab; Andaru Bahy, Moh. Buny; Nasution, Sahkholid; Ahmad Karnel, Muhammad Iqbal (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study contributes significantly to the development of Sharaf learning by introducing an innovative approach using the Ristek Muslim digital dictionary. The guidelines developed in this research provide Arabic language students with an accessible and effective tool to improve their understanding of Sharaf, a crucial component of Arabic grammar. This study enhances student engagement and learning outcomes by integrating digital resources into Sharaf's instruction. The positive feedback from students, material experts, and media experts highlights the value of these guidelines in improving both the content and delivery of Sharaf lessons. Furthermore, the T-test results demonstrate the effectiveness of the digital dictionary guidelines in fostering a more profound comprehension of Sharaf concepts. This contribution supports the modernization of Arabic language teaching, offering a more interactive and efficient way for students to master the intricacies of Sharaf. The findings suggest that integrating digital tools in Arabic language learning, particularly in the study of Sharaf, can contribute to better learning outcomes. Additionally, based on the Borg and Gall model, the development process successfully addressed potential challenges and refined the product through multiple stages of testing and validation. Overall, this study demonstrates that the Ristek Muslim digital dictionary guidelines are a valuable resource for improving Sharaf learning and can be a model for integrating digital technology into Arabic language education